Implementation of Non-Formal Education Based on Rural Communities - Ainul Hayat; Kawakibul Qamar; Tri Candra Wulandari (Journal of Nonformal Education, 2024)
Nonformal education was implemented by Pelita Hati Foundation to empower community, particularly in rural areas. This study seeks to provide a detailed and comprehensive description of the situation and experiences of the community in the implementation of the Pelita Hati Foundation’s nonformal education program, from the perspective of rural communities in Sumenep. Using a qualitative descriptive methodology, the research aims to offer an in-depth understanding of the Pelita Hati Foundation’s nonformal education program in rural areas. The results indicate that the Foundation plays a multidimensional role in both education and community development. It manages various educational institutions, catering to both formal and nonformal education needs. The nonformal education programs run by the Foundation have proven effective in empowering local communities. Furthermore, the collaboration between the Foundation and the community has significantly enhanced local enthusiasm for corn cultivation. With the assurance of reliable buyers offering competitive prices and the potential for multiple harvests per year, corn farming has become a lucrative and attractive economic activity for the community. The Pelita Hati Foundation has successfully implemented an effective nonformal education program that has had a positive impact on the community, particularly in improving their economy and overall well-being. This research contributes valuable insights into the role of nonformal education in community empowerment in rural areas. It also underscores that collaboration between educational institutions and local communities can lead to significant positive impacts on the progress and welfare of the community.